Reliability and usefulness of the 30-15 intermittent fitness test in sub-elite adolescent soccer players - McBurnie, A. J.; Badby, A. J.; dos Santos, T. (Sport Performance & Science Reports, 2019)
The 30-15 Intermittent Fitness Test (30-15IFT) has been introduced as an alternative to commonly administered eld tests for intermittent team sports (1-4) and is popular for its ability to provide a more global assessment of tness specific to team sports (i.e., aerobic and anaerobic capacity, inter-effort recovery ability, anaerobic speed reserve, and change of direction ability) (5). Although evidence suggests the 30-15 IFT is a valid and reliable measure in a variety of team sports (5-8), disparities appear to exist between what is considered a meaningful adaptation within di erent sporting contexts (6-11). Furthermore, no data seems to be publicised in relation to sub-elite adolescent soccer players. Thus, more data needs to be made available in this regard to enable scientists and practitioners to make informed evaluations and training prescriptions that are more specific to their athletic population (i.e., sporting discipline, playing level, age, etc.).